The Discourse System Recognized In The Jakarta Post’s Opinion Coloumn Entitled “Polycarpus Out On Parole: Resolve Munir’s Case” On December 05th, 2014 - Maslihatul Umami (IAIN Salatiga, 2013)
This study attempts to construe the discourse devices recognized in the article of Jakarta Post opinion column entitle ―Polycarpus out on Parole: Resolve Munir‘s Case‖ on December 05th, 2014 using meta-function strategy proposed by Martin and White (2005). The researcher found that the opinion text displays meta-function devices in different ways by using appraisal, ideation, conjunction, identification and periodicity to express their opinion with the related issue. The biggest parts used in appraisal are affect-attitude, judgment-attitude, and appreciation-attitude, force-graduation and focus-graduation. Besides using mono-gloss, the writers of the article also use hetero-gloss by projection, modality and concession or counter-expectancy. In the aspect of ideation, the researcher found that there are four kinds of figures, respectively, ‘doing, saying, sensing, and being. In terms of conjunction, it has been found that the writers of article use external and internal conjunction. To keep track of what is being talked about to the readers, the writers of article using ideation strategies by presenting, presuming, possessive, comparative, and text. At last, in terms of periodicity, the writers use themes, marked themes, and new in order to make the readers easier to grasp the meanings and the plot in the article. Keywords: Jakarta Post opinion article; meta-function system; appraisal; conjuction; ideation; periodicity.